Against Interpretation: Georgia O'Keeffe and 'the Zen of Aestheticism'. Issue 1 (2nd January 2021) - Garland, Sarah
Abstract: Georgia O'Keeffe's reputation as exemplary American innocent was part of the persona that circulated along with her work and with her photographic portraits, throughout her career. This essay argues that O'Keeffe's stylisation of her life and work was a response to early twentieth-century structures of interpretation, and argues that, through reference to Far Eastern metaphysics as they appeared in America in the universalized design principles of Arthur Wesley Dow and Ernest Fenollosa's work in particular, as well as to American traditions of 'plain speech', O'Keeffe used a formalist, aestheticist version of a Far Eastern-inspired aesthetic to pre-empt and parry contemporary psychoanalytic readings of her work and person.